Peningkatan Keaktifan dan Hasil Belajar IPA Melalui Strategi Team Game Tournament - Siti Angimatun (Nur Science Institute, 2021)
This study aims to increase the activeness and learning outcomes of science through the Team Games Tournament (TGT) strategy for the sixth grade students of SD Negeri Mangkubumen Kulon No. 83 semester 1 of the 2017/2018 academic year. This classroom action research was conducted at SD Negeri Mangkubumen Kulon No. 83 in Semester 1 of the 2017/2018 academic year. The research subjects were 20 grade VI students of SD Negeri Mangkubumen Kulon No. 83. The method used in this research is a class action research method which is carried out in 2 cycles through 4 stages, namely (1) planning, (2) implementation, (3) observation, (4) reflection. In the implementation of classroom action research using observation sheets and learning outcomes tests. Data analysis used comparative descriptive analysis technique. The results of this study indicate that the use of the Team Games Tournament (TGT) strategy can increase the activeness and learning outcomes of science class VI SD Negeri Mangkubumen Kulon No. 83 Semester 1 of the 2017/2018 Academic Year.